Rola terenów wiejskich w rozwoju sukiennictwa szadkowskiego w XV-XVII wieku - Marszał, Tadeusz (Biuletyn Szadkowski, 2015)
In 15th and 16th centuries Szadek was one of important towns of the eastern part of Greater Poland and a major centre of wool cloth production of the country, second only to Brzeziny in the Sieradz and Łęczyca district. Such intensive growth of this type of manufacturing activity in Szadek would not have been possible without favourable locational conditions, i.e. local availability of both raw material and labour, which is what for two centuries was supplied to Szadek by the surrounding agricultural areas. This factor certainly contributed to the growth of the town in 15th and 16th centuries, but reliance of wool cloth manufacture on local supply of raw material and unqualified labour force also had its negative aspect. Wool supplied by local sheep-farmers was of poor quality, which affected the type of cloth manufactured in Szadek - it mainly produced cheap, low quality coarse cloth, which was mainly absorbed by local rural market. Economic crisis and worsening of the material situation of peasants, and consequent decreased demand for wool cloth was among the factors which led to the decline of cloth manufacture in Szadek.